A novel model to characterize postnatal exposure to lipophilic environmental toxicants and application in the study of hexachlorobenzene and infant growth. (December 2015) - Stigum, Hein; Iszatt, Nina; Polder, Anuschka; Mandal, Siddhartha; Eggesbø, Merete
Abstract: Background: Infants are exposed to persistent environmental contaminants through breast milk, yet studies assessing the health effects of postnatal exposure are lacking. Existing postnatal exposure assessment is either too simple (lactation exposure model, LEM) or requires complex physiologically-based pharmacokinetic (PBPK) models. Objectives: We present equations for postnatal exposure calculations. We applied these equations to study the effect of hexachlorobenzene (HCB) on infant growth in the two first years of life. Methods: HCB was measured in breast milk samples in 449 mother-child pairs participating in the Norwegian birth cohort study HUMIS. We used these concentrations, mother's weight, height and age, together with child's weight at 8 age points, and proportion of milk consumed each month, to calculate HCB concentrations in the infant over age. We then estimated the association between HCB and infant growth using a linear mixed model. Results: Children exposed to HCB via mother's milk reached concentrations 1–5 times higher than the mother. HCB was associated with lower weight gain in the first 2 years (− 33 g per unit HCB and month, 95% CI: − 38, − 27 at 6 months). Associations were stronger during the first 3 months (− 57 g per unit HCB and month, 95% CI: − 67, − 49 at 1 month), indicating a critical window of effect. Our equations gave more precise estimates than the LEM. Conclusion: Our equations for postnatal exposure of lipophilic environmental toxicants give better results than the LEM and are easier to implement than the complex PBPK models. HCB exposure, especially during the first three months of life, has a negative effect on infant growth up to 2 years. Highlights: Infants are exposed to persistent environmental contaminants through breast milk. We present equations for postnatal exposure calculations of hexachlorobenzene (HCB). We then estimated the association between HCB exposure and infant growth using a linear mixed model. HCB was associated with lower weight gain in the first 2 years of life. Our equations for postnatal exposure are easier to implement than the complex PBPK models.